Fish embryo acute toxicity (FET) test - Walter-Rohde, Susanne; Braunbeck, Thomas (OECD guidelines for the testing of chemicals, 2013)
The test method described in this Test Guidelineis inteneded to determine the acute or letal toxicity of chemicals on embryonic stages of fish (Danio rerio). Newly fertilised zebrafish eggs are exposed to the test chemical for a period of 96 hrs. Every 24 hrs. Twenty embryos (one embryo per well) are exposed to the chemical tested at each concentration level. The test includes five increasing concentrations of the chemical tested and a control. Every 24 hours, four apical observations are recorded as indicators of lethality: (i) coagulation of fertilised eggs, (ii) lack of somite formation, (iii) lack of detachment of the tail-bud from the yolk sac, and (iv) lack of heartbeat. At the end of the exposure period, acute toxicity is determined based on a positive outcome in any of the four apical observations recorded, and the LC50 is calculated. The test report also includes a number of other important information elements related to the conduct of the test, in particular: the concentration of dissolved oxygen, pH, total hardness, temperature et conductivity of solutions, measured concentrations of the chemical tested, and whether the validity criteria of the test were met.
Gesehen am 22.04.2015